Radiology of abdominal emergencies for vascular affections - Curuchet, Eduardo (Cirugía del Uruguay, 1972)
It is analyzed in the simple radiography the radiological signs that provoke the retroperitoneal hematoma by the opening of aneurysms of the aorta and the signs that appear in the spontaneous hemaperitoneum. Afterwards it is described minutely the radiographical images that produce the mesentery intestinal infarct, according to the extension, localization, grade of haematic infiltration of the wall and different aetiologies of the same. These signs are clasified into two groups: 1) Specifics: a) changes of thickness and configuration of the mucous relief; b) gas in the intestinal wall sistem and the portal vein; c) segmentary tightness in the colon enlargment of the wall and defects of stuff at the leve! of the mucous.. 2) No specificss a) distribution and increasing of thethe intestinal gas; b) liquid levels in the small intestine. F'inally are studied the radiographics images angiographic obtaü1ed in the. various causes of the intestinal infarct mesentery: a) atheroma of the main mesentery; b) em bolism; c) stenosis by extrinsic causes; d) fibromuscular· hyperplasia; e) no occlude infarct; f) thrombosis of the ·veins.